Visum Dalam Pembuktian Tindak Pidana Pencabulan Anak: Studi Putusan No.1300/Pid.Sus/2021/Pn.Lbp - Ambarita, Nela; Batubara, Sonya Airini; Wijaya, Wilson; Hasibuan, Belman; Fitriani (Legalite : Jurnal Perundang Undangan dan Hukum Pidana Islam, 2024)
This study examines the verdict of the Lubuk Pakam District Court Case Number 1300/Pid.Sus/2021/PN.Lbp related to a sexual abuse case by the defendant Hasanuddin, who used deception and lies. The focus of the research is the role of the medical report (visum) as evidence in the Indonesian Penal Code (KUHP) and the judge's consideration of using visum in sentencing. This article is classified as a literature study with a qualitative approach. The methodology used is normative legal study. The research findings indicate that the status of the visum in sexual abuse cases is considered valid and has high evidentiary value. The judge considered the visum along with witness testimony and assessed their correlation in supporting the criminal act, resulting in Hasanuddin being found guilty in accordance with the charges brought by the Public Prosecutor.